Digital Leadership for Sustainable Development in Tangerang City - Aditya, Toddy; Aryadillah, Rezky; Dwiyanto, Adie; Firdausi, Lulu (Journal of Local Government Issues, 2025)
The purpose of this research is to find out how digital leadership can affect sustainable development in Tangerang City. The Tangerang City Regional Government has a key role in encouraging digital leadership for sustainable development, and must also ensure the development of adequate digital infrastructure, such as internet networks, data centers, and integrated data management systems to support a reliable digital ecosystem. The variables in this study are digital leadership, and sustainable development. This study uses a quantitative research method with a descriptive approach. Primary data is obtained through the distribution of questionnaires, while secondary data is obtained from books, articles, newspapers and online magazines and others. Hypothesis conclusions, based on the regression results, there is not enough evidence to support the hypothesis that digital leadership has a significant effect on sustainable development in Tangerang City. The absence of this significant influence can be interpreted as the implementation of digital leadership in Tangerang City has not been able to have a direct and strong impact on the achievement of sustainable development. Recommendations to improve sustainable development include the development of digital literacy and capacity through intensive training programs for leaders and staff, the improvement of adequate and secure digital infrastructure, and the implementation of a collaborative approach involving the government, the private sector, academia, the media, and the community in the sustainable development agenda.